2020
DOI: 10.1057/s41310-020-00083-0
|View full text |Cite
|
Sign up to set email alerts
|

Audit partner quality, audit opinions and restatements: evidence from Iran

Abstract: We study whether audit partner quality in the preceding year plays a role in restatements and audit opinions in the current year. Audit failure rate is used as a measure of audit partner quality. A dataset of Iranian listed firms consisting of 1188 observations for the years 2012-2017 is used as the sample. Multivariate analysis reveals that audit partner quality is negatively associated with restatements and issuance of a clean opinion. In addition, this negative association is stronger for the engagement par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Existen trabajos que tratan sobre los socios de auditoría desde distintos enfoques. El tema más recurrente es el de la rotación de los socios firmantes y su relación con la calidad de auditoría (Kuang et al, 2020;MohammadRezaei et al, 2021;Chang et al, 2019;Krishnan & Zhang, 2019;Gómez-Aguilar et al, 2018). Otros temas destacables son el de la relación entre el género de los socios y la calidad de auditoría (Soepriyanto et al, 2020;Lee et al, 2019); el efecto de la carga de trabajo en el comportamiento de los socios (Chen et al, 2020); la experiencia del socio firmante y la calidad de auditoría (Sonu et al, 2019) y más concretamente sobre la experiencia en un sector específico (Garcia-Blandon et al, 2020).…”
Section: Número De Socios Firmantesunclassified
“…Existen trabajos que tratan sobre los socios de auditoría desde distintos enfoques. El tema más recurrente es el de la rotación de los socios firmantes y su relación con la calidad de auditoría (Kuang et al, 2020;MohammadRezaei et al, 2021;Chang et al, 2019;Krishnan & Zhang, 2019;Gómez-Aguilar et al, 2018). Otros temas destacables son el de la relación entre el género de los socios y la calidad de auditoría (Soepriyanto et al, 2020;Lee et al, 2019); el efecto de la carga de trabajo en el comportamiento de los socios (Chen et al, 2020); la experiencia del socio firmante y la calidad de auditoría (Sonu et al, 2019) y más concretamente sobre la experiencia en un sector específico (Garcia-Blandon et al, 2020).…”
Section: Número De Socios Firmantesunclassified
“…The study's findings demonstrated that the public accounting firm's audit quality increased with the length of the audit period. According to Mohammad Rezaei et al [30], the goal of their research is to determine how fake audits affect the independence, impartiality, integrity, and effectiveness of audits. The study was focused on the group of public accounting firm auditors who perform audits for the same company.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considerations include changes, the industry, firm size, locations, and audit service providers. Additionally, according to Mohammad Rezaei et al [30], the audit performed by the public accounting firm is of greater quality the longer the audit term is.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Iran provides a unique setting for examining the role of the number and type (nature and repetitiveness) of AQPs on ARL. More specifically, the release of modified opinions is considerably more frequent in Iran than in other countries (about 31% in Greece; Tsipouridou & Spathis, 2014), with about 60% of all audit opinions issued between 2012 and 2017 being modified (see, MohammadRezaei, Faraji, & Heidary, 2021).…”
Section: Introductionmentioning
confidence: 99%